Variability in Baleen Whale Acoustical Ecology: Implications for Optimal Monitoring Using Passive Acoustics - Recalde Salas, Angela Paola (Curtin University, 2020)
This study aimed to improve the acoustical ecology knowledge of humpback and pygmy blue whales migrating through Geographe Bay - Western Australia. Vocalisations produced by each species were described. Vocalisation rates and detection probabilities varied between species and were dependent on temporal, behavioural and ecological parameters. Correlations between sound energy and visual observations were low for both species. This information suggests that optimal monitoring protocols for passive acoustics should be species specific.